2018
DOI: 10.1016/j.bja.2017.11.082
|View full text |Cite
|
Sign up to set email alerts
|

Emergency care of patients receiving non-vitamin K antagonist oral anticoagulants

Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs), which inhibit thrombin (dabigatran) and factor Xa (rivaroxaban, apixaban, edoxaban) have been introduced in several clinical indications. Although NOACs have a favourable benefit-risk profile and can be used without routine laboratory monitoring, they are associated-as any anticoagulant-with a risk of bleeding. In addition, treatment may need to be interrupted in patients who need surgery or other procedures. The objective of this article, developed by a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(34 citation statements)
references
References 83 publications
0
26
0
7
Order By: Relevance
“…Медиана максимальной степени нейтрализации антикоагулянтного эффекта в течение 4 часов составила 100%. При этом в ситуациях, связанных с проведением экстренного хирургического лечения или неотложной процедуры, общая медиана времени с момента введения первого флакона идаруцизумаба до проведения хирургического лечения составила около 1,5 часов [3]. Следует отметить, что перипроцедурный гемостаз, согласно оценке оперирующего хирурга, был нормальным более чем в 93,4% случаев.…”
Section: плановая хирургияunclassified
“…Медиана максимальной степени нейтрализации антикоагулянтного эффекта в течение 4 часов составила 100%. При этом в ситуациях, связанных с проведением экстренного хирургического лечения или неотложной процедуры, общая медиана времени с момента введения первого флакона идаруцизумаба до проведения хирургического лечения составила около 1,5 часов [3]. Следует отметить, что перипроцедурный гемостаз, согласно оценке оперирующего хирурга, был нормальным более чем в 93,4% случаев.…”
Section: плановая хирургияunclassified
“…Для всех остальных случаев появляется необходимость нейтрализовать его действие. Особенности строения и фармакокинетики дабигатрана дают возможность включить в алгоритмы неотложной помощи применение гемодиализа, позволяющего извлечь из кровотока этот препарат [17]. Для остальных лекарств единственно возможным путем борьбы с тяжелыми и угрожающими жизни кровотечениями остается введение концентрата факторов свертывания крови.…”
Section: действия при кровотеченияхunclassified
“…et al reported a favourable benefit-risk profile for the use of DOACs. However, they are still associated, as are any anticoagulants, with a significant risk of bleeding [22].…”
Section: Rivaroxaban Antidotes Against Overdose or Bleedingmentioning
confidence: 99%
“…It was suggested by J.W. Eikelboom et al [22] that fresh frozen plasma cannot be used to negate the bleeding effect as large volumes are needed. Prothrombin complex concentrates (PCCs) are purified and viral inactivated concentrates of vitamin K-dependent coagulation factors, which are obtained from pooled normal plasma [24].…”
Section: Rivaroxaban Antidotes Against Overdose or Bleedingmentioning
confidence: 99%
See 1 more Smart Citation